Evaluation of the effectiveness of the boiled extract, regular and nano oil of some medicinal plants and their effect on the eggs and larvae of the third phase of date moth Ephestia Cautella (Walk.) (Lepidoptera:Pyralidae) in laboratory conditions - Afrah Denar Hadi; Majeed Miteb Dewan; Thaer Mahmoud Taha (Kufa Journal for Agricultural Sciences)
The experiment was conducted under laboratory conditions, in the insect lab at the College of Science for Girls / University of Kufa in 2021.In order to test the effect of extracts, regular and nano-oil of cinnamon, Cinnamomum zeylanicu, turmeric Curcuma longa and Elettaria cardamomum on the eggs and larvae of the third phase of date moth. Where the three nano-oils excelled on mortality eggs, where the mortality rate of eggs was 100% compared to the regular oil and the boiled extract. The nano-oils were also missed in mortality rate of the third phase larvae after 72 treatments. The Nano cinnamon oil  was excelled in mortality larvae, where the mortality rate was 94.4%, compared to “turmeric nano oil and nano cardamom oil, respectively, as it reached 89.2 and 61.8% at 2% concentration.